THE EFFECTS OF PRISON REFORMS ON REFORMATION OF INMATES IN NYANDARUA COUNTY,KENYA - NJOROGE, PAULINE (Advances in Social Sciences Research Journal, 2020)
This paper uses data collected for an MA Thesis on effects of prison reforms on reformation of inmates in Nyandarua County prisons, Kenya. This study has been necessitated by the need to make the penal system fair and effective. As has been revealed by this study, despite undertaking prison reforms, the attempt to improve the harsh prison conditions has created other problems that negate the reformation and rehabilitation of offenders. The study sought to investigate the effects of prison reforms on reformation of inmates in prisons with a focus on examining the existing prison reforms that have been undertaken in prisons since 2001, the effects of prison reforms on the reformation of prisoners, how Prison reforms have negated the reformation of prisoners, and mechanisms that were in place in prisons to control the negative effects of prison reforms. Major research findings obtained revealed that, though reforms have been implemented, a good portion of the reforms remained un-implemented. This may be explained by the fact that the prison authorities themselves did not put in place deliberate measures to rehabilitate inmates. Besides, there were gaps in the marketability of the skills that the prisoners acquired while in prison. The study noted the upsurge of prison crimes such as substances and drug abuse, rape and sodomy, and prisoner violence/assaults against other prisoners. The study recommends promotion of prison staff because they are the first line of defense in terms of government reformation efforts. Their stronger good will counts in any prisons reformation agenda. The study recommends constant review of prison education and training programmes to conform them to current job market skills for smooth re-integration of prisoners back into the society.